Linguistic Analysis of Jokes in Social Media - Ziyayeva Kamolaxon Ziyaiddinovna (NAZARIY VA AMALIY FANLARDAGI USTUVOR ISLOHOTLAR VA ZAMONAVIY TA’LIMNING INNOVATSION YO’NALISHLARI, 2025)
The rise of social media platforms has transformed communication, allowing humor to flourish in new and diverse ways. Jokes on social media are often short, pithy, and designed to generate rapid engagement through likes, shares, and comments. This phenomenon has garnered attention from linguists, sociologists, and communication experts, leading to an interest in the linguistic elements that characterize jokes in online spaces. In this article, we explore the linguistic strategies employed in jokes on social media, analyzing how language constructs humor and shapes online interaction.